Keterlibatan Orang Tua dalam Perkembangan Sosial Emosional Anak Usia Dini - Dominggus Lero Bili (Journal of Cross Knowledge, 2023)
This research aims to determine the effect of parental involvement on the social emotional development of early childhood. Parents are the first and main people who educate and interact directly with children. The good and bad of an educational institution will be seen through collaboration with parents. This ensures that parental involvement greatly contributes to children's social emotional development, for example children are easy to share, cooperate, help, empathize, assist, discipline and be responsible. The form of parental involvement in early childhood education is that parents participate in school activities, build cooperation between teachers and other adults, and form cooperation with the community to optimize children's development. This research uses quantitative methods with an ex-post facto type of research. The sampling technique in this research was purposive sampling with 146 parents who had young children as participants. Data is collected through market and observation guidelines. Questionnaires are used to collect data on parental involvement, while observation guidelines are used to determine children's social emotional development achievements. The results of this study show that parental involvement has a significant effect on children's social emotional development with a percentage of 0.477%. So it can be concluded that the better the involvement of parents, the better the child's social emotional development.